Expression Analysis of GRHL3 and PHLDA3 in Head and Neck Squamous Cell Carcinoma - Saffarzadeh N (Cancer Management and Research, 2020)
Negin Saffarzadeh,1 Soudeh Ghafouri-Fard,2 Zahra Rezaei,1 Keyvan Aghazadeh,3,4 Farzad Yazdani,4,5 Mehdi Mohebi,2 Mohsen Ahmadi,6,7 Abbas Shakoori,1,8 Javad Tavakkoly-Bazzaz1 1Department of Medical Genetics, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Medical Genetics, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Head and Neck Surgery Research Center, Tehran University of Medical Sciences, Tehran, Iran; 4Otolaryngology Research Center, Amiralam Hospital, Tehran University of Medical Sciences, Tehran, Iran; 5Department of Pathology, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran; 6Booali Medical Research Center, Qom, Iran; 7Booali Office of USERN, Universal Scientific Education and Research Network (USERN), Qom, Iran; 8Department of Medical Genetics, Cancer Institute of Iran, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Abbas Shakoori; Javad Tavakkoly-Bazzaz Tel/Fax +98 2188953005Email shakooria@sina.tums.ac.ir; tavakkolybazzazj@tums.ac.irBackground: Head and neck squamous cell carcinoma (HNSCC) includes a group of heterogeneous tumors with generally invasive behavior. The PI3K/AKT pathway plays an important role in the pathogenesis of HNSCC.Methods: In the current study, we investigated the expression of two negative feedback regulators of the PI3K pathway, namely PHLDA3 and GRHL3, in 45 paired samples of HNSCC and adjacent non-cancerous tissues (ANCTs).Results: While expression of GRHL3 was down-regulated in tumoral tissues compared with ANCTs by the factor 4.21, PHLDA3 expression levels were up-regulated by 5.99-times. Gender-based analysis revealed a significant down-regulation of GRHL3 gene expression level in male patients compared with the control samples and significant up-regulation of PHLDA3 gene expression level in both sexes compared with the control samples. Differences in the expressions of both genes were significant in patients aged more than 60 years, but not in the younger patients. Expression of GRHL3 was only down-regulated in patients with positive smoking history. Expression of GRHL3 was decreased in grades 2 and 3 samples compared with controls. There was a significant increase in transcript levels of PHLDA3 in stages II and III HNSCC samples compared with the controls group. ROC curve analysis indicated that the expression level of PHLDA3 could be a promising marker for the diagnosis of HNSCC patients with a sensitivity and specificity of 0.666 and 0.688, respectively. In addition, sensitivity and specificity of GRHL3 were 0.755 and 0.577, respectively.Discussion: The current study indicates dysregulation of regulators of PI3K pathway in HNSCC and their potential application as putative biomarkers for this cancer.Keywords: GRHL3, PHLDA3, head and neck squamous cell carcinoma